A highly durable CoOx/N-doped graphitized-nano-diamond electrocatalyst for oxygen reduction reaction. (11th June 2021) - Li, Qiang; Zhang, Kehao; Wang, Hailong; Zhang, Jianan; Shao, Gang; Zhu, Jinpeng; Liu, Wen; Fan, Bingbing; Xu, Hongliang; Lu, Hongxia; Zhou, Yanchun; Zhang, Rui; et al.
Abstract: Oxygen reduction reaction (ORR) occupies a pivotal position in fuel cell applications, and it is a challenge to obtain highly durable ORR catalysts. Herein, porous cobalt oxide microsphere growing at the surface of on nitrogen-doped graphitized-nano-diamond (CoO x /N-GND) was prepared using hydrothermal and subsequent heat treatment process. Porous cobalt oxide of high specific surface area could expose more surface Co 2+ that act as active sites than bulk one does. The doping of nitrogen also promotes the catalytic activity. Besides, nano-diamond (ND) of sp 3 hybrid structure was used as an electronic conduction carriers of ultrahigh stability to improve the durability of catalytic composite. Prepared CoO x /N-GND shows a satisfactory half-wave potential of 0.82 V (versus RHE), which is close to that of Pt/C (0.85 V), an excellent methanol tolerance and a lower activity loss after 5000 cycles. These merits inspire the application of CoO x /N-GND as the cathode of Zn-air battery and the battery performance was evaluated in this work. In general, this work highlights an innovate approach to design and prepare highly durable catalyst.